HUBUNGAN STATUS GRAVIDA DENGAN KEJADIAN PREEKLAMPSIA DI WILAYAH KERJA PUSKESMAS NGASEM KABUPATEN KEDIRI - Triatmi Andri Yanuarini; Suwoyo Suwoyo; Tinta Julianawati (JURNAL KEBIDANAN, 2020)
Preeclampsia is a pathological pregnancy that is a health problem in the mother and baby it contains. Preeclampsia is the second leading cause of death in pregnancy in the world. Preeclampsia can adversely affect both the mother and the fetus it contains. Maternal complications include HELLP syndrome (Hemolysis, Elevated Liver Enzyme, Low Platelet), pulmonary edema, renal impairment, bleeding, placental abruption and even maternal death. One of the factors that influence the occurrence of preeclampsia is the status of gravida.The purpose of this research is to know the relation of gravida status with preeklampsiadi occurrence at work area of ​​Ngasem health center. The design of correlational research with data collection was done by using case control method, with population of1,191 data of pregnant women patients in January - December 2016, sampling using simple random sampling technique with 50 data of patient who fulfilled inclusion criteria. Chi Square test with significant level 0,05 indicates that value of ρ value <α (0,038 <0,05). The conclusion of this research is there is relationship of gravida status with incident of preeclampsia at work area of ​​health center of Ngasem Regency of Kediri.It is recommended especially in pregnant women to routinely check their pregnancy and follow the integrated ANC to detect early preeclampsia. Keywords: Mother, Gravida, Preeclampsia